2021
DOI: 10.1177/17423953211039778
|View full text |Cite
|
Sign up to set email alerts
|

Online Self-Disclosure and Social Sharing of Emotions of Women with Breast Cancer Using Instagram–Qualitative Conventional Content Analysis

Abstract: Objectives Women with breast cancer share their experiences and emotions about the illness on Instagram – a tool understudied when it comes to chronic illness. The paper characterizes the women's activities, and both online self-disclosure and social sharing of emotions concepts are used to help explain the women's practices. Methods Using qualitative conventional content analysis, four profiles of women are manually analysed, with posts as the unit of analysis ( n  =  811). Based on eleven subcategories, thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…The research continues the work done by the first author (Pluta, 2021) on online selfdisclosure of women with breast cancer using Instagram, with self-disclosure understood as the willingness to provide intimate, private information about oneself (e.g., Barak & Suler, 2008). Previously, Pluta showed that Instagram posts are full of fears, anxiety, pain, weaknesses, and suffering associated with the treatment and body changes (C1: Category 1-self-disclosure of negative information).…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…The research continues the work done by the first author (Pluta, 2021) on online selfdisclosure of women with breast cancer using Instagram, with self-disclosure understood as the willingness to provide intimate, private information about oneself (e.g., Barak & Suler, 2008). Previously, Pluta showed that Instagram posts are full of fears, anxiety, pain, weaknesses, and suffering associated with the treatment and body changes (C1: Category 1-self-disclosure of negative information).…”
Section: Introductionmentioning
confidence: 66%
“…Also, this approach is deductive and guided by a more structured process than a conventional approach. Thus, the codebook was developed based on prior research on Instagram (Pluta, 2021) with previously identified categories and subcategories (the three categories indicated above and 10 subcategories).…”
Section: Methodsmentioning
confidence: 99%
“…Qualitative methods, such as in-depth interviews and semi-structured interviews, can provide a rich and nuanced understanding of self-disclosure behaviour, including the context and emotions involved, and allows researchers to practice induction and theory building (e.g., Klim et al, 2021;Pluta, 2021). Differently from interview-based techniques, which are specifically designed as part of an experimental manipulation to elicit self-disclosure under controlled conditions focusing on the effects of specific variables, interviews in qualitative research serve as a qualitative instrument for data elicitation (Vondracek, 1969).…”
Section: Elicitation Techniquesmentioning
confidence: 99%
“…Further analysis of the disclosure content through automated and manual text analysis methods could provide deeper insights into the emotional content conveyed in participants' disclosures to the robot. Conducting a more comprehensive textual analysis using advanced computational techniques [see 143,144] and manual evaluation [e.g., [145][146][147] could offer valuable insights and context to participants' self-disclosures to the robot [93]. Although the study did not utilise manual coding of self-disclosure, the behavioural paradigm employed was specifically designed to encourage self-disclosure by asking participants questions about personal matters.…”
Section: The Challenges Of Measuring Self Disclosure and Well-beingmentioning
confidence: 99%